The load of hepatitis B virus reduces the immune checkpoint inhibitors efficiency in hepatocellular carcinoma patients - Ji, Zhengzheng; Li, Jiasong; Zhang, Shasha; Jia, Yuanyuan; Zhang, Jing; Guo, Zhanjun (Frontiers in Immunology, 2024)
IntroductionChronic viral infection may lead to an immunosuppressive microenvironment, whereas the association between virus-related indicators and treatment response in hepatocellular carcinoma(HCC) patients undergoing immune checkpoint inhibitors(ICIs) therapy remains a topic of debate. We aim to investigate the influence of hepatitis virus on the ICI efficiency in HCC patients through a meta-analysis.MethodsWe searched PubMed, Cochrane Library, Embase, and Web of Science until 14 July 2024 to identify cohort studies involving ICIs treatments in HCC patients. We extracted data from the literature related to hepatitis B virus (HBV) infection, hepatitis C virus (HCV) infection, baseline HBV load, and antiviral therapy. Overall survival (OS) and progression-free survival (PFS) were considered as the primary endpoints, while objective response rate (ORR) was regarded as a secondary endpoint.ResultsWe included 55 cohort studies published between 2019 and 2024, involving a patient population of 7180 individuals. Summarized hazard ratio (HR) comparing HBV infection with non-HBV infection in the context of ICIs therapy revealed no significant association between HBV infection and either mortality risk or progression risk with the pooled HR for OS of 1.04(95%CI: 0.93-1.16, P=0.483) and the pooled HR for PFS of 1.07(95%CI:0.96-1.20, P=0.342). HBV infected patients with HCC may have better tumor response than non-HBV infected patients receiving ICIs with the combined relative risk(RR) for ORR was 1.94 (95%CI: 1.12-3.38, P=0.002). High baseline HBV load is associated with poor survival outcomes in patients with HCC who receive ICIs with the pooled HR for OS was 1.74 (95%CI: 1.27-2.37, P=0.001), thereby antiviral therapy has the potential to significantly enhance prognostic outcomes with the pooled HR for OS was 0.24 (95% CI: 0.14-0.42 P<0.001) and the pooled HR for PFS was 0.54 (95% CI: 0.33-0.89 P=0.014).ConclusionIn individuals with HCC who received ICIs, there was no notable link found between HBV or HCV infection and prognosis. However, HBV infection showed a connection with improved tumor response. A higher initial HBV load is linked to worse survival results in HCC patients undergoing ICIs treatment and antiviral therapy can significantly improve its prognosis.